Surgical Navigation, Augmented Reality, and 3D Printing for Hard Palate Adenoid Cystic Carcinoma En-Bloc Resection: Case Report and Literature Review - García-Sevilla, Mónica; Moreta-Martinez, Rafael; García-Mato, David; Arenas de Frutos, Gema; Ochandiano, Santiago; Navarro-Cuéllar, Carlos; Sanjuán de Moreta, Guillermo; Pascau, Javier (Frontiers in Oncology, 2022)
Adenoid Cystic Carcinoma is a rare and aggressive tumor representing less than 1% of head and neck cancers. This malignancy often arises from the minor salivary glands, being the palate its most common location. Surgical en-bloc resection with clear margins is the primary treatment. However, this location presents a limited line of sight and a high risk of injuries, making the surgical procedure challenging. In this context, technologies such as intraoperative navigation can become an effective tool, reducing morbidity and improving the safety and accuracy of the procedure. Although their use is extended in fields such as neurosurgery, their application in maxillofacial surgery has not been widely evidenced. One reason is the need to rigidly fixate a navigation reference to the patient, which often entails an invasive setup. In this work, we studied three alternative and less invasive setups using optical tracking, 3D printing and augmented reality. We evaluated their precision in a patient-specific phantom, obtaining errors below 1 mm. The optimum setup was finally applied in a clinical case, where the navigation software was used to guide the tumor resection. Points were collected along the surgical margins after resection and compared with the real ones identified in the postoperative CT. Distances of less than 2 mm were obtained in 90% of the samples. Moreover, the navigation provided confidence to the surgeons, who could then undertake a less invasive and more conservative approach. The postoperative CT scans showed adequate resection margins and confirmed that the patient is free of disease after two years of follow-up.